Data analysis and learning analytics for measure effects of gamification in a math online project - Lopes, Ana Paula (2018)
Nowadays the use of the information and communication technologies (ICT) is more and more common in the learning and teaching process. Modern forms of education have risen and these require the implementation of new learning paradigms: situated cognition, student-centred learning, distributed cognition, constructivism, and communities of practice, among others. However there is an important problem that concerns educators, the lack of student motivation and engagement in education, especially in the e-learning environment (Online Education, Online Courses), where the motivation and the active role of students are definitely the key. Therefore, the interest of researchers in the subject of gamification, which main pillars are motivation, progressiveness and instant feedback, has increased. Furthermore, influence of gamification, depending on utilized components (challenge, curiosity, competion, recognition, etc) may have different effects on students. Thus, there is a need of deeper understanding of dependencies between engagement and implemented gamification elements. The goal of such analysis could be personalization of an e-learning system based on a model that enables management of gamification process individually for every student. The purpose of this paper is to investigate how gamification affects a Mathematics Online Course that is using this model as a pedagogical strategy. It relates such strategy with active learning practices and discusses its effectiveness, investigating how gamification can motivate students to participate more deeply and even to change their self-concept as learners. Moreover, the learning analytics and data analysis shows that implementation of the gamification components contributes to the engagement of students in an e-learning environment, having a positive impact on the final grade.